Catalogue of type specimens of invertebrates in the collection of the Instituto Nacional de Pesquisas da Amazônia, Manaus, Brazil. IV. Arachnida: Acari, Palpigradi, Pseudoscorpiones, Ricinulei and Schizomida - Saturnino, Regiane; Tourinho, Ana Lúcia; de Azevedo, Clarissa Salette; Magalhães, Célio (Zootaxa, 2009)
An updated catalogue of type specimens of Acari, Palpigradi, Pseudoscorpiones, Ricinulei and Schizomida deposited in the Invertebrate Collection of the Instituto Nacional de Pesquisas da Amazônia (INPA), Manaus, Brazil, is presented. A total of 19 holotypes and 23 lots of paratypes of 22 species of Acari; three lots of paratypes of one species of Palpigradi; 28 holotypes and 209 lots of paratypes of 30 species of Pseudoscorpiones; two holotypes and two lots of paratypes of two species of Ricinulei; and five holotypes and two lots of paratypes of six species of Schizomida are listed. Scientific names are listed alphabetically by family, followed by bibliographic citation, type status, collection number, locality data, collector, and collecting date.